Droplet digital PCR vs. quantitative real time-PCR for diagnosis of pulmonary and extrapulmonary tuberculosis: systematic review and meta-analysis - Meregildo-Rodriguez, Edinson Dante; Asmat-Rubio, Martha Genara; Vásquez-Tirado, Gustavo Adolfo (Frontiers in Medicine, 2023)
Tuberculosis is a rising global public health emergency. Then, it is a priority to undertake innovations in preventive, diagnostic, and therapeutic methods. Improved diagnostic methods for tuberculosis are urgently needed to address this global epidemic. These methods should be rapid, accurate, affordable, and able to detect drug-resistant tuberculosis. The benefits of these new diagnostic technics include earlier diagnosis and treatment, improved patient outcomes, and reduced economic burden. Therefore, we aimed to systematically review the diagnostic performance of droplet digital PCR (ddPCR)-a third-generation PCR-compared with quantitative Real Time-PCR (qPCR) for diagnosing pulmonary and extrapulmonary tuberculosis.We included 14 diagnostic accuracy test studies performed in Asia, Europe, and Latin America, 1672 participants or biological samples, and 975 events (pulmonary or extrapulmonary tuberculosis). Most of the included studies had a low risk of bias (QUADAS-C tool). Sensitivity and specificity were lower for ddPCR [0.56 (95% CI 0.53-0.58) and 0.97 (95% CI 0.96-0.98), respectively] than for qPCR [0.66 (95% CI 0.60-0.71) and 0.98 (95% CI 0.97-0.99), respectively]. However, the area under the ROC curve (AUC) was higher for ddPCR than for qPCR (0.97 and 0.94, respectively). Comparing both AUCs using the Hanley & McNeil method, we found statistically significant differences (AUC difference of 4.40%, p = 0.0020). In the heterogeneity analysis, we found significant differences between both techniques according to the continent of origin of the study and the location of tuberculosis (pulmonary or extrapulmonary disease). The AUCs of both methods were similar in pulmonary tuberculosis. However, for extrapulmonary tuberculosis, the AUC was higher for ddPCR. We found some limitations: 1) significant heterogeneity of the studies, and 2) we could not perform subgroup analyses according to other relevant variables, such as the age and sex of the participants. Nonetheless, this study is the first meta-analysis that shows that ddPCR has a comparable diagnostic performance than qPCR for pulmonary tuberculosis. However, for extrapulmonary tuberculosis, ddPCR has a better discriminant capacity to differentiate between patients with and without extrapulmonary tuberculosis.We conclude that ddPCR is likely the best diagnostic technic for tuberculosis diagnosis, especially for extrapulmonary tuberculosis. More studies are still needed yet.